TAFSIR EKOLOGIS DAN PROBLEMATIKA LINGKUNGAN: (Studi Komparatif Penafsiran Mujiyono Abdillah Dan Mudhofir Abdullah Terhadap Ayat-Ayat Tentang Lingkungan) - Ahmad Zainal Abidin; Fahmi Muhammad (Institut Agama Islam Negeri (IAIN) Keiri, 2020)
Ecological interpretation is an interpretation made with the object of Quranic verses related to ecological themes, using ecology-based scientific analysis, with a nuance of partiality towards environmental problems. The formulation of environmental preservation in the perspective of the Quran is a necessity, as conceived by Mujiyono Abdillah and Mudhofir Abdullah. This is related to the function of the Quran as a source of values in Islam that has a high concern for environmental problems. it could even be said to be an environmentally sound holy book. The method used in this paper is descriptive-analytical. This paper finds that: 1) Mujiyono Abdillah made an ecological interpretation as the basis for developing the concept of eco-theology in response to environmental problems. 2) Mudhofir Abdullah made ecological interpretation as the basis for developing eco-sharia concepts as an alternative solution to environmental problems.